Komunikasi Synchronous dan Asynchronous dalam Blended Learning Pasca Pandemi - Solihin, Rahmat (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Blended learning requires a robust communication pattern to create effective learning. So educational institutions inevitably have to use technology media in education. This makes a new communication that must be thoroughly discussed. So the purpose of this research is to know the perception and compare the synchronous and asynchronous communication used in blended learning in the post-pandemic period. This study uses a comparative descriptive method, data sources obtained from observations, and literature studies from various relevant sources. Based on the results of research conducted, it is known that learning with synchronous and asynchronous communication must be combined to obtain optimal learning effectiveness. To combine these two types of communication, it is necessary to pay attention to aspects related to the point of learning in blended learning because by choosing the right platform, media, attributes, and learning model, effective education will be realized.